Transcriptional analysis of arogenato dehydratase genes identifies a link between phenylalanine biosynthesis and lignin biosynthesis. - El-Azaz-Ciudad, Jorge; De-la-Torre-Fazio, Fernando Nicolás; Pascual-Moreno, María Belén; Debille, Sandrine; Harvengt, Luc; Trontin, Jean-François; Ávila-Sáez, Concepción; Cánovas-Ramos, Francisco Miguel (Oxford Academic, 2020)
Biogenesis of the secondary cell wall in trees involves the massive biosynthesis of the phenylalanine-derived polymer lignin. Arogenate dehydratase (ADT) catalyzes the last, and rate-limiting, step of the main pathway for phenylalanine biosynthesis. In this study, we found that transcript levels for several members of the large ADT gene family, including ADT-A and ADT-D, were enhanced in compression wood of maritime pine, a xylem tissue enriched in lignin. Transcriptomic analysis of maritime pine silenced for PpMYB8 revealed that this gene plays a critical role in coordinating the deposition of lignin with the biosynthesis of phenylalanine. Specifically, it was found that ADT-A and ADT-D were strongly down-regulated in PpMYB8-silenced plants and that they were transcriptionally regulated through direct interaction of this transcription factor with regulatory elements present in their promoters. Another transcription factor, PpHY5, exhibited an expression profile opposite to that of PpMYB8 and also interacted with specific regulatory elements of ADT-A and ADT-D genes, suggesting that it is involved in transcriptional regulation of phenylalanine biosynthesis. Taken together, our results reveal that PpMYB8 and PpHY5 are involved in the control of phenylalanine formation and its metabolic channeling for lignin biosynthesis and deposition during wood formation in maritime pine.
Keywords: Biosíntesis; Genetica vegetal; Fenilalanina; Lignina; Arogenato; Phenylalanine; Lignin